Komodifikasi Tradisi Silat Muna (Ewa Wuna) di Desa Lakarinta Kecamatan Lohia Kabupaten Muna - Hazlan; Rahmat Sewa Suraya; La Ode Marhini (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2023)
This study aims to understand the commodification of Muna Silat, a traditional martial art, in Lakarinta Village, Muna Regency. It uses qualitative methods, such as observation, in-depth interviews, and documentation. The results show that Muna Silat is still alive and preserved as a cultural heritage that is passed down to the younger generation. It also adapts to the modern era and becomes a popular attraction in various events. The training fee for Ewa Wuna, a type of Muna Silat, is 150 thousand, but there are no additional costs during the training. The performance fee varies, depending on the duration and location of the show. The equipment rental fee is 500 thousand for all the tools used.